Nucleolar size in lymphocytes and haemocytes of different species - Berger, Josef (European journal of histochemistry, 2008)
The number of nucleoli in a cell and nucleolar area vary according to the cell. We compared nucleoli in mammalian circulating lymphocytes and insect circulating haemocytes. An increased nucleolar coefficient correlated with a lowered nucleoli size. The smaller nucleolar size in mammalian lymphocytes indicates a lower proteosynthetic cellular activity in both mammalian lymphocytes and insect haemocytes. Moreover, in insect haemocytes, the smaller size of the nucleoli may reflect a lowered potential to transform into another cell type.
Keywords: zvířata; Cell Nucleolus; Animals; buněčné jadérko; Adult; Mice; lymfocyty; Rats; Hemocytes; Middle Aged; Insecta; lidé středního věku; Adolescent; Humans; myši; hmyz; Lymphocytes; dospělí; hemocyty; Helminths; mladiství; lidé; cizopasní červi; krysa rodu Rattus